Targeting a Low-Teen Intraocular Pressure by Trabeculectomy With a Fornix-Based Conjunctival Flap: Continuous Japanese Case Series by a Single Surgeon. Issue 3 (March 2015) - Aoyama, Yuka; Murata, Hiroshi; Aihara, Makoto
Abstract : Purpose: To examine the medium-term outcomes of fornix-based trabeculectomy (TLE) performed by a single surgeon and to analyze outcome in 3 glaucoma subtypes. Methods: Consecutive prospective case series study to examine the 6-month outcome of 106 eyes [primary open-angle glaucoma (OAG), exfoliation glaucoma (XFG), and inflammatory glaucoma (ING)] that underwent TLE with mitomycin C performed by a single surgeon from September 2009 to September 2010 at Tokyo University Hospital. Main outcome measure was survival rates of targeted intraocular pressure (IOP) after TLE. Postoperative complications and procedures were analyzed according to glaucoma subtypes. Life table analyses were then made according to 2 criteria of failure: (1) IOP was >12 mm Hg with or without the use of topical glaucoma medications after 2 consecutive measurements or another surgery was needed; and (2) IOP was >15 mm Hg. Results: A total of 106 eyes, which consisted of 67 OAG eyes, 23 XFG eyes, 16 ING eyes, were analyzed for 6 months after TLE. Four eyes were reoperated. During and after hospitalization, complications were equally observed and procedures were equally performed in all of the 3 groups. For the first definition, cumulative survival rates at 6 months after surgery in OAG, XFG, and ING cases were 76.0%, 73.9%, and 62.5%, respectively. For the second definition, cumulative survival rates in OAG, XFG, and ING cases were 88.0%, 78.3%, and 68.8%, respectively. Conclusions: Six-month outcome of TLE with a fornix-based conjunctival incision by a single surgeon that targeted an IOP<12 mm Hg was not different among 3 types of glaucoma.